Load Deflection Relationship of a Solid Slab under the Action of Construction Loads - Eriya Kigoye; Michael Kyakula (Advances in Civil Engineering)
Over the past decades, there has been a tremendous improvement in the concrete placement technology in Uganda. The methods have moved from being manual to the use of concrete pumps. A concrete pump is capable of pumping high volumes of concrete per minute. This implies that for small volume slabs before the setting of concrete, the whole weight of the fresh concrete of the upper slab, formwork, and props is transferred to the lower supporting slab. During construction, slabs are stacked with materials like bricks, blocks, sand, and aggregates. Construction loads such as block loads and loads due to props, formwork, and freshly cast solid concrete slabs on the lower floor are usually greater than the imposed loads and are not catered for in design. A baseline survey carried out on 118 randomly selected sites in Kampala revealed that in 87% of the cases, supports are removed from a lower reinforced concrete slab, and then props are put on its top to support a yet to be cast slab on an upper floor. It also revealed that 80.6% of the slabs had construction loads such as bricks, blocks, sand, timber, and aggregates. Deflections were measured using dial gauges for construction loads owing to freshly cast slab and concrete blocks in a physical model of a multistory structure with dimensions of 4 m long, 2 m wide, 2 m high to 2nd level, and 2 m to 3rd level. Loads due to freshly cast concrete were 158% more than unfactored design live loads. The maximum deflection at center of the slab due to a freshly cast slab and blocks loaded instantly was 1.15 mm and 11.815 mm, respectively, compared to the immediate deflection equal to 0.103 mm due to a design-imposed load of 2 KN/m2.